2021
DOI: 10.1038/s41598-021-85684-7
|View full text |Cite
|
Sign up to set email alerts
|

Triangulating evidence from longitudinal and Mendelian randomization studies of metabolomic biomarkers for type 2 diabetes

Abstract: The number of people affected by Type 2 diabetes mellitus (T2DM) is close to half a billion and is on a sharp rise, representing a major and growing public health burden. Given its mild initial symptoms, T2DM is often diagnosed several years after its onset, leaving half of diabetic individuals undiagnosed. While several classical clinical and genetic biomarkers have been identified, improving early diagnosis by exploring other kinds of omics data remains crucial. In this study, we have combined longitudinal d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Increased fasting levels of the aromatic amino acid phenylalanine and threonine have also been associated with diabetes [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Recent evidence employing the Mendelian randomization method has confirmed a causal role of several amino acids’ disrupted metabolism in the development of insulin resistance [ 42 ]. Additionally, lower glutamine levels or glutamine-to-glutamate ratio are associated with a higher risk of diabetes [ 36 , 39 , 40 ] and a worse cardiometabolic profile [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased fasting levels of the aromatic amino acid phenylalanine and threonine have also been associated with diabetes [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Recent evidence employing the Mendelian randomization method has confirmed a causal role of several amino acids’ disrupted metabolism in the development of insulin resistance [ 42 ]. Additionally, lower glutamine levels or glutamine-to-glutamate ratio are associated with a higher risk of diabetes [ 36 , 39 , 40 ] and a worse cardiometabolic profile [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms related to how mannose increases the risk of T2D remain unknown. Recently, an MR study confirmed that mannose is causally associated with T2D [53].…”
Section: Population-based Studiesmentioning
confidence: 97%
“…From a mechanistic perspective, the human milk metabolome has the potential to influence infant growth via several distinct mechanisms, including direct interactions between individual milk biochemicals and infant intestinal or immune cells, nutritional effects (e.g., providing higher or lower amounts of essential amino acids or vitamins), effects of absorbed metabolites on distant organs, effects on the developing infant microbiome and other pathways. The possibility of metabolome—microbiome interactions is supported by a recent study by Ribo et al, which found reduced levels of betaine (a one‐carbon metabolite previously linked to cardiovascular and diabetes risk 62,63 ) in milk from obese mothers 64 . Betaine supplementation of mouse dams resulted in increased betaine content in milk, and long‐term improvements in metabolic health of offspring including decreased adiposity and improved glucose tolerance, via a microbiome‐dependent mechanism.…”
Section: Review Of Non‐nutritive Componentsmentioning
confidence: 98%